Developing a Culturally Appropriate Assessment Tool: Reflections on Process Considerations. Issue 4 (1st October 2016) - Weaver, Hilary N.
ABSTRACT: This article describes the process of modifying an assessment tool in order to make it culturally appropriate for South Asian Tamil refugees and asylum seekers. This was envisioned as an important step in giving practitioners who work with Tamils a useful tool and advancing the knowledge base on cultural competence to make it more inclusive of instrument development. This article provides a detailed description of how the instrument was developed, thus addressing a significant deficiency in the literature.